(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The construction industry is, after agriculture, the second biggest employer with 33 million workers. Long-term percentages of people working are analphabets, unskilled, untrained and migrant most are agricultural. Until installation at construction sites, there is no proven realistic system of screening staff. In tandem with this, general physical and precarious working environments and elevated risk capacity are rendering construction industries more vulnerable to accidents. There have been rampant accidents that lead to loss of life and body pots. Health has also been a big concern in the building sector. Construction, in particular in developing countries such as India, is considered dangerous in terms of safety and health criteria.